Accelerated variety turnover for open-pollinated crops in Tanzania - Phase 1 Key Findings - Ochieng, Justus; Rubyogo, Jean Claude; Birachi, Eliud Abucheli; Radegunda, Kessy; Masimane, Joy; Mbugua, Mercy; Odhiambo, Wilfred; Mutua, Mercy; Kitoto, Victor O.; Steinke, Jonathan; Munguatosha, Ngomuo; Daudi, Happy; et al. (International Center for Tropical Agriculture, 2023)
Open-pollinated varieties (OPVs), such as beans, sorghum, and groundnuts, are important for increased income, job creation, food security, and nutrition of both urban and rural households in sub-Saharan Africa (SSA). However, the main constraint is underdeveloped seed systems, which contribute substantially to dwindling productivity among small-scale farmers due to limited access to reliable and quality planting materials. ACCELERATE is expected to accelerate varietal adoption and turnover in Tanzania by tapping into the power of large/small-scale or marketplace traders, and institutional seed buyers.